FACE-Q Head and Neck Cancer Questionnaire for Brazilian Portuguese: Translation, Cross-Cultural Adaptation, and Linguistic Validation - Vitor Penteado Figueiredo Pagotto; Rodolfo Costa Lobato; Adriana Margarita Buelvas Bustillo; Cristiane Pereira Lopes; Rafael Mamoru Carneiro Tutihashi; Fábio de Freitas Busnardo; Rolf Gemperli (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: Head and neck neoplasms often affect fundamental functions, such as swallowing, speech, eating, and socializing. Evaluating their treatment should consider the physician’s opinion and the patient’s perspective. This difficulty in assessing the success of treatment led to the development of the FACE-Q Head and Neck Cancer Module, a questionnaire of patient-reported outcomes that measure the appearance, facial function, quality of life, and experience of care to head and neck neoplasms. The objective is to translation, cultural adaptation, and linguistic validation of the FACE-Q Head and Neck Cancer questionnaire for Brazilian Portuguese. Methods: The translation, cultural adaptation, and linguistic validation of the full questionnaire took place in four stages, using official guidelines from the World Health Organization and the International Society of Pharmacoeconomics and Outcomes Research. Results: A semantic, idiomatic, and conceptually equivalent Brazilian Portuguese version was achieved through a linguistically validated translation of the English FACE-Q Head and Neck Cancer module. Conclusion: The Brazilian Portuguese version presents a version equivalent to the original English instrument, which can be used as a critical patient-reported outcome assessment.